Surface Characteristics and Mechanical Performance of EPDM/Graphene Oxide Composites - Ahmad Allahbakhsh (علوم و تکنولوژی پلیمر)
Hypothesis: The employment of graphene oxide (GO) in polymer composites has garnered significant interest due to its potential applications in the aerospace construction, and electronics industries. This is due to the proven potential of graphene oxide to enhance the mechanical, functional, and electrical properties of polymer-based composite materials. Additionally, the surface properties of polymer composites are directly influenced by the structural and mechanical properties of these materials.Methods: The mechanical and surface properties of ethylene propylene diene monomer (EPDM)/GO composites are investigated. graphene oxide , prepared in powder form, was mixed with EPDM at loading contents of 1, 3, and 5 phr using a two-roll mill. The main objective was to investigate the effect of graphene oxide loading content on the tear strength and surface roughness of EPDM/GO composites through surface and mechanical analyses.Findings: Results indicate that the incorporation of graphene oxide in a loading content of 3 phr leads to a significant improvement in mechanical properties. More than 75% increase in tensile strength, 5% increase in the elongation-at-break, and more than 16% rise in the tear strength are achieved when 3 phr GO is loaded into the structure of EPDM. The incorporation of graphene oxide also results in a slight improvement in the modulus of the system. Based on the atomic force microscopy and tensile test results presented in this work, a direct relationship between surface behavior and mechanical properties of EPDM/GO composites is observed.